Hand-held lactate analyzer as a tool for the real-time measurement of physical fatigue before slaughter and pork quality prediction. (17th November 2014) - Rocha, L. M.; Dionne, A.; Saucier, L.; Nannoni, E.; Faucitano, L.
Abstract : The objectives of this study were to assess the relationship between blood lactate variation measured at the plant, and pork quality variation on a large sample size and under commercial preslaughter handling conditions. A total of 600 pigs were randomly chosen on arrival at a commercial slaughter plant and blood samples taken from the ear vein at unloading (UN), after lairage (LA), in the restrainer (RE; before stunning) and at exsanguination (EX) were analysed for lactate content using a Lactate Scout Analyzer (LSA). In order to have a large range of measures, pigs were distributed into two groups; one kept in lairage overnight (G1) and the other for 2 to 3 h (G2) before slaughter. Meat quality was assessed in the Longissimus thoracis (LT), Semimembranosus (SM) and Adductor (AD) muscles by measuring the pH 30 min postmortem (pH1) and at 24 h postmortem (pHu), the colour and the drip loss. Blood lactate levels did not differ between G1 and G2 ( P >0.05). A reduced muscle lactate and glucose contents ( P =0.02 and P =0.004, respectively) resulting in a lower ( P <0.001) glycolytic potential (GP) was observed in the LT muscle of G1 pigs when compared with G2 loins. In the LT muscle of G1 pigs, the lower GP resulted in an increased pHu ( r =−0.67; P <0.001), decreased drip loss ( r =0.57; P <0.001) and darker colour ( r =0.50; P <0.001) compared with G2. In both G1 and G2 pigs, the lower GP was correlated to higher pHu value in the SM and AD muscles ( r =−0.73; P <0.001). The greatest correlation was observed in G2 between blood lactate levels at LA and pHu value of the SM and AD muscles ( r =0.46 and r =0.44, respectively; P <0.001 for both muscles). The second greatest correlation was found between blood lactate levels at EX and pH1 value in the SM muscle in both groups ( r =−0.37 and r =−0.41, respectively; P <0.001 for both groups). Based on the results of this study, it appears that blood lactate levels, as measured by the LSA, reliably reflect the physiological response of pigs to perimortem stress and may help explain the variation in pork quality.